2019
DOI: 10.1016/j.ejca.2019.08.032
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review and network meta-analysis of effectiveness and safety outcomes in advanced melanoma

Abstract: BACKGROUNDAlthough a myriad of novel treatments entered the treatment paradigm for advanced melanoma, there is a lack of head-to-head evidence. We conducted a network meta-analysis (NMA) to estimate each treatment's relative effectiveness and safety. METHODSA systematic literature review (SLR) was conducted in Embase, MEDLINE, and Cochrane to identify all phase-III randomised controlled trials (RCTs); timeframe: January 1, 2010 to March 11, 2019. We retrieved evidence on treatment-related grade 3/4 adverse eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 65 publications
3
46
0
4
Order By: Relevance
“…In the multivariate Cox regression analysis, we identified LDH, S-100B, ECOG-PS and number of MBM as independent prognostic factors. These prognostic factors have already been described in previous analyses, 8 14 39-41 but to the best of our knowledge, S100B has only been described as independent prognostic factor for checkpoint inhibitor immunotherapy in one monocentric study. 42 It is interesting, however, that both tumor markers, LDH and S100B, remained independent prognostic factors in the multivariate analysis, suggesting that these non-invasive and easy to determine blood parameters can and should be used early in the course of the disease to inform about patients' prognosis.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In the multivariate Cox regression analysis, we identified LDH, S-100B, ECOG-PS and number of MBM as independent prognostic factors. These prognostic factors have already been described in previous analyses, 8 14 39-41 but to the best of our knowledge, S100B has only been described as independent prognostic factor for checkpoint inhibitor immunotherapy in one monocentric study. 42 It is interesting, however, that both tumor markers, LDH and S100B, remained independent prognostic factors in the multivariate analysis, suggesting that these non-invasive and easy to determine blood parameters can and should be used early in the course of the disease to inform about patients' prognosis.…”
Section: Discussionsupporting
confidence: 53%
“…5 With the introduction of targeted treatment (BRAF/MEK inhibitors) and immune checkpoint inhibitors, the prognosis of metastatic melanoma has drastically improved. [6][7][8] In contrast to ample data on the efficacy of Open access novel therapies in stage IV melanoma without MBM, there are only a few small studies on the efficacy of these drugs in patients with cerebral disease. This lack of information is mainly due to the fact that large phase II/III multicenter studies systematically excluded patients with MBM, particularly if symptomatic or previously treated with local therapy, such as stereotactic radiosurgery and surgery (STR/surgery).…”
Section: Introductionmentioning
confidence: 99%
“…Melanoma is the most common malignant skin tumor with a high mortality rate. Drugs targeting BRAF mutations such as vemurafenib, dabrafenib and PD-1 monoclonal antibodies, including pembrolizumab and nivolumab have greatly improved the prognosis of melanoma [ 71 , 72 ]. Gallardo treated melanoma cells with IVM and found that it could effectively inhibit melanoma activity [ 73 ].…”
Section: The Role Of Ivm In Different Cancersmentioning
confidence: 99%
“…One study showed that NF1 mutations suppress BRAF targeted therapy making BRAF inhibitors less efficient against BRAF and NF1 double mutants [406]. The therapeutic agents used for melanoma treatment have been reviewed recently [407]. Below we discuss resistant mutations that arise in response to some of these agents.…”
Section: Classificationmentioning
confidence: 99%